Inculcating Heart Intelligence in English Communication Workshop for Day-care Educators - Airin, Abdul Ghani; Haslinda, Hashim; Anita, Abdul Rani; Noor Raha, Mohd Radzuan; Fatimah, Ali; Wan Jumani, Fauzi; Noor Azlinda, Zainal Abidin; Ezihaslinda, Ngah; Siti Farhana, Haron (2017)
Teaching is a noble job. However, not everyone aspires to become a teacher. Many join the teaching force as a last resort for want of a job. For early childhood education, this can be detrimental as literature shows that early learning requires special attention because it lays the foundations for lifelong learning. Heart Intelligence is a module which introduces Spiritual and Emotional Intelligence, enhanced by the notion of `Man as Caliph (i.e. leader)’ and his role to harmonise and protect the world. This Heart Intelligence module enhances the beliefs and understanding of spiritual, emotional and social skills of the educators. The purpose of this study is to examine how this module gives impact to the educators and how it helps the educators to have more control on their job engagement. A qualitative research design was employed to collect data through interviews and reflection from 29 educators who voluntarily participated in this study. Participants were required to apply the elements of Islamic teaching during English Communication Module and apply them to their students when they get back to their workplace. They provided positive feedback especially after they have implemented the Heart Intelligence module inside the classrooms. From the responses, there were positive changes in the educators especially when dealing with their students at school. The module helps them to decrease stress at workplace, work better with the students and feel satisfied with their job. They also suggested some new ideas for the module throughout the teaching and learning session as to introduce the concept of human and `caliph’.